Relationship of particular matter and temperature on the risk of adverse events in atrial fibrillation patients. (25th November 2020) - Rivera-Caravaca, J.M; Roldan, V; Vicente, V; Lip, G.Y.H; Marin, F
Abstract: Background: Ambient particulate matter (PM), is a principal component of air pollutant and the main culprit of the adverse effects of air pollution on humans' health. In particular, PM with aerodynamic diameter <10 μm (PM10) has been shown to be associated with worse clinical outcomes. Similarly, cardiovascular risk increases during colder temperatures/seasons. Thus, both, air pollution and temperature fluctuations are examples confirming how the climate change is affecting our health. However, our knowledge about the impact of air pollution and temperature in anticoagulated atrial fibrillation (AF) patients is scarce. Purpose: Herein, we investigated if PM10 and temperature are associated with an increased risk of adverse clinical outcomes in patients with AF taking vitamin K antagonists (VKAs). Methods: We included AF patients who were stable on VKAs (INR 2.0–3.0) for 6 months in a tertiary hospital (Murcia, South-east Spain). During a median follow-up of 6.5 (IQR 4.3–7.9) years, ischemic strokes, major bleeds, adverse cardiovascular events, and mortality were recorded. From 2007–2016, data on average temperature and PM10 (PM with aerodynamic diameter <10 μm) were obtained and related to clinical outcomes. Results: 1361 patients (48.7% male; median age 76, IQR 71–81 years) were included. High PM10 and low temperatures were associated with higher risk of major bleeding (adjusted Hazard Ratio, aHR 1.44, 95% CI 1.22–1.70 and aHR 1.03, 95% CI 1.01–1.05) and mortality (aHR 1.50, 95% CI 1.34–1.69 and aHR 1.04, 95% CI 1.02–1.06) (Table 1). PM10 was also significantly associated with ischemic stroke and temperature with cardiovascular events. The relative risk for cardiovascular events and mortality increased in months in the lower quartile (Q1) of temperature (<12.74°C) (RR 1.12, 95% CI 1.04–1.21 and RR 1.41, 95% CI 1.15–1.74; respectively). Comparing seasons, there were higher risks of cardiovascular events in spring, autumn, and winter than in summer, whereas the risk of mortality increased only in winter. Conclusions: In AF patients taking VKAs highPM10 and low temperature were associated with an increased the risk of ischemic stroke and cardiovascular events, respectively. Both factors increased major bleeding and mortality risks, which were higher during colder months and seasons. Funding Acknowledgement: Type of funding source: None